Low-complexity and frequency-offset-robust synchronization algorithm based on CAZAC sequence - Fengkui GONG; Ni WEN; Guo LI; Yang GAO (Tongxin xuebao)
A low-complexity and frequency-offset-robust synchronization algorithm based on CAZAC sequence was proposed, which was suitable for burst OFDM systems.A new preamble sequence was constructed based on the CAZAC sequence, and its simplified timing metric function was derived by using the combination characteristics of the sequence, and then the delay correlation and symmetric correlation characteristics were used to achieve accurate and stable timing synchronization.Furthermore, based on the new constructed preamble sequence, a weighted frequency synchronization scheme combining cyclic prefix was proposed to obtain more accurate frequency offset estimation.Simulation results show that the proposed algorithm has good synchronization performance in both Gaussian channels and multipath fading channels regardless of frequency offset, and its computational complexity is lower than the most existing representative algorithms.